2018
DOI: 10.1002/jcp.26413
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from human embryonic stem cell‐MSCs ameliorate cirrhosis in thioacetamide‐induced chronic liver injury

Abstract: Various somatic tissue-derived mesenchymal stromal cells (MSCs) have been considered as an attractive therapeutic tool for treatment of liver diseases in which the secretion of soluble factors or extracellular vesicles (EVs) is the most probable mechanism. The experimental application of human embryonic stem cell-derived MSC (ES-MSC) increased rapidly and showed promising results, in vitro and in vivo. However, possible therapeutic effects of human ES-MSC and their EVs on Thioacetamide (TAA)-induced chronic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 80 publications
1
92
1
Order By: Relevance
“…MSC-derived EVs were able to reduce fibrosis in CCl4-and thioacetamide-induced chronic liver injures by alleviating hepatic inflammation and collagen deposition and by inhibiting epithelial-to-mesenchymal transition. [27][28][29][30] Moreover, EVs derived from serum reduced liver fibrosis in mice treated with CCl4 or thioacetic acid by improving liver function, reducing hepatocyte apoptosis, and suppressing inflammation. 31 These recent papers indicate that EVs can be exploited for therapy in liver diseases.…”
Section: Discussionmentioning
confidence: 97%
“…MSC-derived EVs were able to reduce fibrosis in CCl4-and thioacetamide-induced chronic liver injures by alleviating hepatic inflammation and collagen deposition and by inhibiting epithelial-to-mesenchymal transition. [27][28][29][30] Moreover, EVs derived from serum reduced liver fibrosis in mice treated with CCl4 or thioacetic acid by improving liver function, reducing hepatocyte apoptosis, and suppressing inflammation. 31 These recent papers indicate that EVs can be exploited for therapy in liver diseases.…”
Section: Discussionmentioning
confidence: 97%
“…A communication between embryos and maternal uterine milieu through secreting signals is required for proper mammalian development (O'Neill, ). Recent studies observed that EVs are secreted from various somatic cells including human embryonic stem cell (Mardpour et al, ), induced pluripotent stem cell (Bobis‐Wozowicz et al, ), ovarian follicle (da Silveira et al, ), and even embryos (Qu et al, ). Our previous study also demonstrated that membrane budding microvesicles from outgrowth embryos improved developmental competence in vitro and the implantation potential of cocultured embryos in utero as well (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…HSC fibrogenesis is stimulated by these types of hepatocyte-derived EVs [29,32,41], while other phenotypic features of activated HSC such as migration and AKT phosphorylation have been shown to be enhanced by EVs from liver sinusoidal endothelial cells [42]. On the other hand, EVs from healthy hepatocytes [43], various stem cells [44][45][46][47][48][49][50][51] or the serum of healthy mice [52] have the ability to inhibit experimental liver fibrosis, largely by suppressing inflammatory responses and/or pathways of activation or fibrogenesis in HSC. The recognition that HSC are EV targets has highlighted an important new mechanism by which fibrogenic pathways in the liver are modulated and has given a new lead for novel anti-fibrotic therapies based on suppressing the action of pro-fibrotic EVs or harnessing the actions of EVs that are intrinsically anti-fibrotic.…”
Section: Discussionmentioning
confidence: 99%